Richard Wagner’s Opera “Tannhäuser” in the Director’s Interpretation of Romeo Castellucci - Honchar, Oleksii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the study lies in the systematization of the expressive means of the director’s interpretation of R. Castellucci, who, using the semantic elements of Dionysianism and Appolonism, Pantheism and Christianity — the main pair of oppositions for the European cultural space, has compared not only the forms of expression, but also the concepts of art, Tannhäuser’s inability to make a choice and be successful. He sees positive elements in each of them, but without accepting them as a whole, always remains on the verge, being rejected by the system, unwilling to completely immerse himself in it. R. Castellucci interprets Tannhäuser’s image as a victim of the conventions of these systems. The novelty of the research lies in the analysis of R. Castellucci’s producing, which is not substantially studied in Ukrainian musicology, although it opens a completely new interpretation of Tannhäuser. The figurative content of the main opposing forces here is fundamentally different from their previous incarnation on the opera stages of the world. The main objective of the study was to penetrate into the general interpretive vision of the work — its maximum symbolization, the use of figurative and semantic elements and their combinations in the work, which constitute the semantic field of the production, having a wide variance of perception and not directly following the plot, avoiding narrative and at the same time not deviating from the author’s text. The theme of love in its sensual and spiritual, as well as art and its forms of expression — the opposition of these criteria by R. Wagner is significantly complicated through the interpretation of them by R. Castellucci in postmodern discourse, where a set of pre-meanings gains direct meaning. So Venus and Venusburg, for R. Wagner, are a symbol of sensuality, and the director exaggerates the sensual to the meaning of “indecent”, where “hyper” becomes the primary characteristic, which is inherent in the elements of the production as a whole. The study was done by using semiotic principles of the director’s work and their semantic load determined the main methodological approaches of research in accordance with the works of J. Baudrillard, which were based on the algorithm for the structural analysis of an opera work developed by M. R. Cherkashina-Gubarenko. Elizabeth is the opposition to this discourse, and the Wartburg society is the personification of excessive rationalization, which makes it mechanized and devoid of humanity, impervious to other points of view, that is, totalitarian. In the end, Tannhäuser and Elizabeth are freed from the irreconcilable tension between discourses, the end of which becomes a deeply symbolic non-existence and stratification of space, time, performer and character. In any case, Tannhäuser does not really renounce his beliefs; the blossom of the bishop’s staff as a sign of divine grace refers not so much to Tannhäuser as to labeling his views as permissible in a variety of opinions, but alien to the clerical spirit and its institutions. As a result we can argue that the director departs from traditional interpretations of the plot and value judgments of a certain world, leaving unanswered the question of the normativity of one of them as opposed to the other, makes filling with symbolic images, while blurring clear lines and avoiding direct definition through illustrative direction. In general, everything hyper-, over-, “too” and “exaggerated” is characteristic of the director’s interpretations of R. Castellucci. His postmodern vision of the theater and some kinship with the “theater of cruelty” A. Artaud, allows, according to R. Castellucci, to experience these emotions outside of real life, to sublimate them through art — which was the focus of ancient tragedy. The study has significance from the point of view of an artistic and scientific description of the modern stage director’s theater, the principles of the artist’s work with material and its adaptation to modernity without violating the author’s intention. It can be used as a material in the studying of directors of musical theater and in introductory courses on modern trends in operatic art.